Design of a cost-effective online experimental platform for electrical experiments using a Raspberry Pi-based system - Abdelkrim Benali; Somia Benali; Benameur Hemidi (Institute of Advanced Engineering and Science, 2026)
Following the COVID-19 pandemic, online learning platforms have become vital for supporting distance education. This work presents LABTEC, an online Experimental Platform for electronics education that enables students to manipulate real hardware through a learning management system (LMS). The platform allows remote execution of experiments with electronic circuits and instruments, such as oscilloscopes, providing hands-on practice over the Internet in real time. The main contributions of this work are threefold: (i) a hybrid Flask–Django server architecture, where flask manages instrument-level control and Django provides secure and scalable web services; (ii) the use of a Raspberry Pi gateway as a cost-efficient and versatile hardware interface; and (iii) an open-source remote laboratory framework experimentally validated to support real-time interaction with average end-to-end latency below 50 ms, stable multi-user access, and low resource utilization. Experimental results demonstrate reliable operation under concurrent user scenarios, achieving consistent measurement visualization and control with reduced deployment cost compared to proprietary and institution-centric remote laboratory platforms. Performance evaluation shows a control latency below 50 ms for closed-loop tasks, a success rate above 98% under multi-user access, and average CPU and RAM usage of 35% and 420 MB on Raspberry Pi 4B during peak load. These results demonstrate that the system is responsive, reliable, and suitable for concurrent experiments. Although validated with a single instrument type, the proposed approach offers a scalable and replicable solution that can significantly enhance electronics education and lower laboratory infrastructure costs.